Incidencia de residuo gástrico alto en pacientes adultos que reciben soporte nutricional enteral en instituciones de alta complejidad de la ciudad de Medellín-Colombia (2010)
High gastric residue (HGR) is a complication for patients receiving enteral nutrition support (ENS), there is a debate about its efficacy and there is no consensus about the cutoff points that can define it. Objective: to estimate the incidence of HGR for patients in intense care unit (ICU) and for hospitalized patients just in a regular bed receiving ENS from hospitals of Medellín-Colombia. Methodology: this is a multicentric descriptive study, the data was obtained from clinical report sources of patients treated in ICU and hospitalized who received ENS. We explored socio-demographic, clinical, and nutritional variables related with the nutritional support. Results: sixty eigth hundred patients were evaluated 62.3% in ICU and 37.7% hospitalized in a regular bed. The incidence of HGR in ICU was 24.3% and 3.9% for patients in regular bed. Significant difference were found (p=0.0000) and RR was 6.2 times higher in patients from ICU. Age, diagnosis, access and support duration showed significant differences in the incidence of HGR in patients from UCI. Conclusion: the HGR is a recurrent complication of ENS; the incidence was significantly higher in patients from UCI compared with patients hospitalized in regular bed. Further studies are necessary to determine the cutoff points, and techniques to assess gastric residue, and to evaluate the impact of the ENS. Key words: enteral nutrition, nutritional support, intensive care, patients hospitalized.